3-Methyl-methcathinone: Pharmacokinetic profile evaluation in pigs in relation to pharmacodynamics. (June 2015) - Shimshoni, Jakob A; Britzi, Malka; Sobol, Eyal; Willenz, Udi; Nutt, David; Edery, Nir
3-Methyl-methcathinone (3-MMC) is a novel, synthetic cathinone analog, recently linked to poisoning events among recreational users. The lack of pharmacological data on 3-MMC, prompted us to explore its pharmacokinetic profile as well as its effect on feeding behavior, weight gain, and serum biochemistry. 3-MMC was administered to male pigs (n=3, three months old) as a single intravenous dose (0.3 mg/kg), followed by a multiple oral dose administration (3 mg/kg) for five days and plasma and tissue concentrations determined. Concomitantly a control group consisting of two healthy male pigs received saline solution instead of 3-MMC according to the same administration schedule. 3-MMC effects on complete blood count, biochemistry, feed intake, and body weight were examined. The pigs were sacrificed and submitted to a pathological and histopathological examination. 3-MMC displayed rapid absorption with a peak concentration achieved within 5–10 min after oral ingestion and a plasma half-life of 0.8 h. The bioavailability was about 7%. 3-MMC tissue levels were below detectable levels 24 h after the last oral dosage. No treatment-related clinical signs were observed and no histopathological findings were detected. 3-MMC caused significant change in daily feed intake and weight gain over time. The animals treated with 3-MMC displayed a lower rate of increase in mean body weight. Caution needs to be practiced in terms of extrapolating the present data to human safety, due to the low sample size, low dosage, and the relatively short study duration as well as the lack of data on abuse potential of 3-MMC.